2022
DOI: 10.1142/s0192415x22500847
|View full text |Cite
|
Sign up to set email alerts
|

Arteannuin B Enhances the Effectiveness of Cisplatin in Non-Small Cell Lung Cancer by Regulating Connexin 43 and MAPK Pathway

Abstract: Cisplatin (DDP)-based chemotherapy is the first-line regimen for advanced non-small cell lung cancer (NSCLC) patients. However, advanced NSCLC patients may have innate resistance to DDP or develop resistance during DDP treatment. We investigated a natural compound, arteannuin B (Art B), for its potential effects on DDP resistance in NSCLC. Art B was isolated from Artemisia annua by chromatographic purification and spectral elucidation. The activities of Art B on DDP-mediated effects were examined using in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…It is interesting to note that KEGG pathway enrichment was observed only in the downregulated group (Figure 5F ; Table S3 ). Among these enrichments, some signaling pathways were commonly related to cisplatin resistance in osteosarcomas, such as the mitogen‐activated protein kinase (MAPK) pathway 20 , 21 , 22 , 23 , 24 and vascular endothelial growth factor (VEGF). 25 , 26 , 27 Additionally, 10 hub genes were identified, and their associated signaling pathways were demonstrated (Figure 5G ).…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that KEGG pathway enrichment was observed only in the downregulated group (Figure 5F ; Table S3 ). Among these enrichments, some signaling pathways were commonly related to cisplatin resistance in osteosarcomas, such as the mitogen‐activated protein kinase (MAPK) pathway 20 , 21 , 22 , 23 , 24 and vascular endothelial growth factor (VEGF). 25 , 26 , 27 Additionally, 10 hub genes were identified, and their associated signaling pathways were demonstrated (Figure 5G ).…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al have reported a novel adjuvant compound, arteannuin B (Art B), that enhances the cytotoxicity of cisplatin by facilitating its uptake into the cancer cells. This is mediated by the upregulation of connexin43, the activation of gap junction and MAPK pathways, and the increase of intracellular Fe2+ and calcium influx 29 …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our hypothesis, a recent study has interestingly highlighted the importance of gap junction activation and MAPK pathways for overcoming cisplatin resistance in NSCLC. 29 Huang et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations